Absorbing Boundary Conditions for Solving N-Dimensional Stationary Schrödinger Equations with Unbounded Potentials and Nonlinearities (Communications in Computational Physics, 2011)
We propose a hierarchy of novel absorbing boundary conditions for the one-dimensionalstationary Schrödinger equation with general (linear and nonlinear) potential.The accuracy of the new absorbing boundary conditions is investigated numericallyfor the computation of energies and ground-states for linear and nonlinearSchrödinger equations. It turns out that these absorbing boundary conditions andtheir variants lead to a higher accuracy than the usual Dirichlet boundary condition.Finally, we give the extension of these ABCs to N-dimensional stationary Schrödingerequations.